Analisis Pengaruh Perubahan Kebiasaan Makan Terhadap Kontinuitas Produksi Telur Itik Di Kabupaten Batu Bara - Misnun, Misnun; Hasnudi, Hasnudi; Siregar, Muhammad Akbar (Universitas Medan Area, 2019)
The purpose of this study was to reveal whether changes in eating habits in laying ducks had a negative influence on the continuity of egg production. Keywords: superior fruits, production value, worthiness. The study was conducted in Batu Bara District by conducting a survey of 35 (thirty-five) breeders in nine villages in three sub-districts. The breeders that are used as the object of research are breeders with intensive and traditional maintenance patterns. This type of research is descriptive quantitative research and the data used are primary data. The method used in data collection uses survey methods through questionnaires. Analysis of the data used in this study is a simple linear regression analysis. The results of this study are changes in eating habits negatively affect the continuity of duck egg production. This explains that there is an opposite relationship between changes in duck eating habits to the continuity of egg production.